Changing antiepilepsy drug-prescribing trends in women with epilepsy in the UK and Ireland and the impact on major congenital malformations. Issue 12 (16th April 2018) - Kinney, Michael O; Morrow, James; Patterson, Chris C; Campbell, Ellen; Russell, Aline; Smithson, Henry W; Parsons, Linda; Morrison, Patrick J; Bromley, Rebecca; Liggan, Brenda; Delanty, Norman; Irwin, Beth; et al.
Abstract : Objectives: After 20 years of data collection, pregnancy registers have informed prescribing practice. Various populations show trends for a reduction in valproate prescribing, which is associated with an increased risk of anatomical teratogenesis and neurodevelopmental effects in those exposed in utero. Our aim was to determine if any shifts in prescribing trends have occurred in the UK and Ireland Epilepsy and Pregnancy Register cohort and to assess if there had been any change in the overall major congenital malformation (MCM) rate over time. Methods: The UK and Ireland Epilepsy and Pregnancy Register, a prospective, observational, registration and follow-up study established in 1996, was used to determine the changes in antiepileptic drugs (AEDs) utilised during pregnancy and the MCM rate between 1996 and 2016. Linear regression analysis was used to assess changes in AED utilisation, and Poisson regression was used for the analysis of trends in the MCM rates. Results: Outcome data for 9247 pregnancies showed a stable percentage of monotherapy to polytherapy prescribing habits over time. After Bonferroni correction, statistically significant (p<0.003) changes were found in monotherapy prescribing with increases in lamotrigine and levetiracetam and decreases in valproate and carbamazepine use. Between 1996 and 2016, the total MCM rate showed a 2.1% reduction per year (incidence risk ratio 0.979 (95% CIs 0.956 to 1.002) but Poisson regression analysis showed that this was not statistically significant p=0.08). Conclusion: Significant changes are seen in the prescribing habits in this cohort over 20 years, but a statistically significant change in the MCM rate was not detected. This work should be replicated on a larger scale to determine if significant changes are occurring in the MCM rate, which would allow a robust economic estimate of the benefits of improvements in prescribing practice and the personal effect of such changes.